Biomimetic synthesis of selenium nanoparticles using cell-free extract of microbacterium sp ARB05 - Prasad, K. S.; Vyas, P.; Prajapati, V.; Patel, P.; Selvaraj, K. (Micro & Nano Letters, 2012)
This Letter is a novel approach to synthesise a bio-functionalised selenium nanoparticles using cell-free extract of selenium-resistant bacterial isolate. Phylogenetic analysis of isolate suggested its close similarity with Microbacterium luteolum (Y17235.1) and Microbacterium oxydans str. TPL09 (EU373379.1) while it was distantly related to Microbacterium dextranolyticum (Y17230.1). Selenium colloidal solution exhibited an absorption maximum at 300 nm and gave emission maximum at 590 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, Se nanoparticles of diameter ranging from similar to 30 to 150 nm. X-ray diffraction results showed 111, 200 and 220 planes of face-centred cubic selenium. Energy dispersive analysis of X-rays confirmed the presence of selenium in nanosphere. Selenium nanoparticles synthesised in this manner can be studied for chemo-prevention as well as its fluorescent property can be utilised for molecular diagnostics in cancer research.